Low-carbon economic dispatch of power system based on mobile hydrogen storage. Issue 1 (1st May 2022) - Li, Panpan; Wang, Rui; Xia, Shiwei; Zhang, Feng
Abstract: To alleviate the global warming crisis, carbon reduction is an inevitable trend of sustainable development. The energy carrier with Hydrogen (H2 ) is considered to be one of the promising choices for realizing a low-carbon economy. With the increasing penetration level of wind power generation and for well-balancing wind generaion fluctuations, this paper proposes a low-carbon economic dispatch method for power systems based on mobile hydrogen storage(MHS). The wind power surplus during off-peak load periods is first utilized to generate green H2 . Afterward, the green H2 is optimally transported to multiple hydrogen storage(HS) stations for generating power electricity by flexibly controlling the electrolysis(EL), methanation(ME), carbon capture(CCS) and H2 power generation processes, in such a way the wind power is coordinated with the hydrogen production, transport and utilization to reduce the total carbon emission and minimize the operation cost of power systems. Finally the proposed power system low-carbon economic dispatch model is verified by case studies.